Early-life management practices and their association with dairy herd longevity, productivity, and profitability - Gabriel M. Dallago; Daniel Warner; Elsa Vasseur (Journal of Dairy Science)
ABSTRACT: Although improving the management of lactating cows to reduce health and reproductive issues can enhance cow longevity, the long-term effects of early-life management practices are less understood. The objectives of this study were to characterize dairy farms based on their early-life management practices and analyze their associations with herd longevity, productivity, and profitability. In this cross-sectional observational study, early-life management practices regarding colostrum feeding, milk feeding, solid feed and weaning, and housing were collected from 1,658 dairy farms in Québec, Canada, using a questionnaire between February 2020 and February 2021. Length of productive life and the percentage of cows in their third or greater lactation, estimated from DHI testing data, were used as herd longevity indicators, whereas lifetime cumulative ECM production and lifetime cumulative milk value, also derived from DHI records, served as indicators of productivity and profitability, respectively. Cluster analysis was performed to characterize farms based on their early-life management practices. Cluster stability assessment was used to determine the best clustering algorithm and number of clusters. Associations between herd longevity, productivity, profitability, and early-life management practices were assessed using multivariate linear regression models. Due to missing data (ranging from 0.1% to 15.4% across variables), multiple imputation was employed, and significant practices were identified by iteratively applying likelihood ratio tests (α < 0.05) across the imputed datasets. Two clusters were identified and denominated as traditionally or modernly managed farms. The traditionally managed farms cluster (n = 600; 36.2%) was characterized by feeding nonpasteurized or nonacidified milk (whole or waste) with individual buckets, not measuring the concentration of IgG in the colostrum, and housing calves individually. Modernly managed farms (n = 1,058; 63.8%) were characterized by feeding calves powdered milk replacer through automated systems and group housing calves both before and after weaning. Practices adopted by traditionally managed farms were associated with increased longevity but lower productivity and profitability, whereas practices adopted by modernly managed farms were associated with lower longevity but increased productivity and profitability. Our results highlight that early-life management practices are linked with herd longevity, productivity, and profitability, but further research is needed to understand the underlying factors contributing to these associations and to guide dairy farmers in making informed management decisions.